Kinetic studies of NO formation in pulsed air-like low-pressure dc plasmas. (30th March 2016) - Hübner, M; Gortschakow, S; Guaitella, O; Marinov, D; Rousseau, A; Röpcke, J; Loffhagen, D
Abstract: The kinetics of the formation of NO in pulsed air-like dc plasmas at a pressure of 1.33 mbar and mean currents between 50 and 150 mA of discharge pulses with 5 ms duration has been investigated both experimentally and by self-consistent numerical modelling. Using time-resolved quantum cascade laser absorption spectroscopy, the densities of NO, NO2 and N2 O have been measured in synthetic air as well as in air with 0.8% of NO2 and N2 O, respectively. The temporal evolution of the NO density shows four distinct phases during the plasma pulse and the early afterglow in the three gas mixtures that were used. In particular, a steep density increase during the ignition phase and after termination of the discharge current pulse has been detected. The NO concentration has been found to reach a constant value of, , and for mean plasma currents of 50 mA, 100 mA and 150 mA, respectively, in the afterglow. The measured densities of NO2 and N2 O in the respective mixture decrease exponentially during the plasma pulse and remain almost constant in the afterglow, especially where the admixture of NO2 has a remarkable impact on the NO production during the ignition. The numerical results of the coupled solution of a set of rate equations for the various heavy particles and the time-dependent Boltzmann equation of the electrons agree quite well with the experimental findings for the different air-like plasmas. The main reaction processes have been analysed on the basis of the model calculations and the remaining differences between the experiment and modelling especially during the afterglow are discussed.